Conservation of the Threatened Arabian Wolf (Canis lupus arabs) in a Mountainous Habitat in Northwestern Saudi Arabia - Abdulaziz S. Alatawi (Biology)
The expansion of human activities can degrade natural habitats, thereby increasing threats to wildlife conservation. The wild populations of many species have declined due to the modification of natural habitats by humans. The Arabian wolf (Canis lupus arabs) is a subspecies of the gray wolf that is of conservation concern across its distribution range. The Arabian wolf is understudied in certain habitats (e.g., mountainous areas), which limits understanding of its overall ecology. Given its vulnerable conservation status, this study aimed to collect relevant data and information on incidents and potential threats facing this predator in the rugged mountainous habitats of western Tabuk province, Saudi Arabia, and how the effects of these threats can be minimized. In these mountain habitats Arabian wolves encounter various severe threats that challenge relevant conservation efforts. Observations of such threats—some of which result in wolf mortality—represent serious challenges to the survival of wild Arabian wolves. Conflicts with humans and livestock represent considerable threats that must be appropriately managed. Additionally, the potential association between Arabian wolves and free-ranging dogs requires further investigation. Various conservation scenarios and mitigation approaches can be applied to help reduce negative impacts on Arabian wolf populations and maximize their likelihood of survival. Overall, ensuring the persistence of such a unique desert-adapted apex predator in this ecosystem must become a conservation priority.